Balanço do nitrogênio e sugestão de adubação nitrogenada para o milho cultivado em sistema de plantio direto - Silva, Helton de Souza (2019)
Nitrogen is the nutrient required in higher quantities by the plants, however, it presents a complex dynamic in the soil-plant system, which result in high losses and low recovery by the plants. Therefore, nitrogen fertilization has to be done in a cautious way in order to minimize losses and maximize productivity. The objectives of this study were: a) to determine the yield of corn submitted to nitrogen fertilization; b) perform the nitrogen balance in the soil-plant system and c) perform the nitrogen fertilization recommendation based on the crop requirement to achieve a projected yield, in a quantity of nitrogen that the soil can supply to the plants and at the expectation of fertilization efficiency. The experiment was composed in the application of three doses of nitrogen (30, 70 and 95 kg ha-1) and a control (without fertilization). The doses were applied in the hybrid corn AG 1051 80 along with 56 kg ha-1 of P2O5 and K2O, respectively. The experiment was arranged in a randomized complete block design with five replications. It was observed that the production of total dry matter had a linear behavior increasing as a function of the nitrogen doses, the same was observed for the grain yield, which reached 5,684.79 kg ha-1. The total nitrogen extraction and the export had a linear behavior increasing according to the nitrogen doses, being obtained in the highest nitrogen dose the extraction of 114.93 kg ha-1 and the export of 79.81 kg ha-1. The recovery of N-fertilizer by the plants increased linearly as a function of the nitrogen doses, obtaining 64.88% of N-fertilizer recovery for the highest dose. The amount of nitrogen supplied by the soil to corn plants of 52.81 kg ha-1 resulted in a mineralization coefficient of 1.2%. The equations used in this work are efficient to perform the nitrogen fertilization recommendation IX for the corn crop, considering that the amount of recommended N (94.33 kg ha-1) using the equations to reach the maximum yield obtained in this work is equivalent to applied dose (95 kg ha-1). Harvest index (IH) and fertilization efficiency (FE) are variable according to the projected yield. Nitrogen availability (NA) and N content in dry matter (NCDM) are constant.